2010
DOI: 10.2494/photopolymer.23.405
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly(3-hexylthiophene)-b-poly(ethylene oxide) for Application to Photovoltaic Device

Abstract: without contamination of PEO-BE which can be removed by reprecipitation in methanol. The polymer structure was confirmed by 1 H and 13 C NMR spectra. The signal assignable to PEO was observed at 3.6 ppm in 1 H NMR spectrum of P3HT-b-PEO. In addition, the signals derived from phenylene ring at the junction point shifted from that of PEO-BE. These results clearly indicate that PEO segment was introduced at the end of P3HT. The weight ratio of P3HT and PEO segments was estimated as 93.1:6.9 from integral ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…We anticipate that it is possible to control the domain size in the composite film consisting of block copolymer and n-type small molecule (PCMB), via self-assembly of the block copolymer, and it also assists the regular alignment of each domain. Previously we reported that the p-type diblock copolymer, Poly(3-hexylthiophene)-b-poly(ethylene oxide) (P3HT-b-PEO) was synthesized by coupling between regioregular P3HT and PEO homopolymers, and that the regular morphology with small size can be obtained in the thin films of P3HT-b-PEO blended with PCBM [17]. A similar strategy using P3HT-b-poly(4-vinylpyridine) was reported independently [18].…”
Section: Introductionmentioning
confidence: 83%
“…We anticipate that it is possible to control the domain size in the composite film consisting of block copolymer and n-type small molecule (PCMB), via self-assembly of the block copolymer, and it also assists the regular alignment of each domain. Previously we reported that the p-type diblock copolymer, Poly(3-hexylthiophene)-b-poly(ethylene oxide) (P3HT-b-PEO) was synthesized by coupling between regioregular P3HT and PEO homopolymers, and that the regular morphology with small size can be obtained in the thin films of P3HT-b-PEO blended with PCBM [17]. A similar strategy using P3HT-b-poly(4-vinylpyridine) was reported independently [18].…”
Section: Introductionmentioning
confidence: 83%
“… 126 Block copolymers, macromolecules with distinguished segments of ionic and electronic conduction, represent another example of the heterogeneous type. 127 While heterogeneous OMIECs are subject to the microphase separation between ion conducting and π-conjugated components, the materials of the homogeneous type do not suffer from this issue. Homogeneous OMIECs generally incorporate charged or polar groups, often through side chain engineering utilizing EG-based moieties, within a single material, producing a bulk mixed conduction phase by distributing ion solvating fragments along the polymer backbone.…”
Section: Materials Development For Oect Applicationsmentioning
confidence: 99%
“…Previously we demonstrated that the hole transporting diblock copolymer P3HT-b-PEO was synthesized by coupling regioregular P3HT and PEO homopolymers, and that the morphology can be controlled in the thin films of P3HT-b-PEO blended with PCBM [41]. We here report that a novel block copolymer consisting of PTPA and polystyrene (PS) was prepared for the application to photovoltaic device.…”
Section: Introductionmentioning
confidence: 94%